A Pre - Experimental Study to Assess the Effectiveness of Information Booklet on the Knowledge Regarding Prevention of Child Sexual Abuse Among Mothers Residing at Selected Urban Areas of Nerchowk, District Mandi ( H.P.) 2025 - Anju Kumari,; Reena Devi,; Renu Devi,; Richa Shukla, (International Journal of Scientific Research in Science and Technology, 2025)
Background: Child sexual abuse (CSA) is a serious global public health and human rights issue with long-lasting physical, psychological, and social consequences for children. It includes both contact and non-contact forms of sexual exploitation that violate a child’s trust, safety, and dignity. Despite legal frameworks like the POCSO Act, India continues to report a rising number of CSA cases, with most offenders being known to the victims. Lack of awareness, stigma, and inadequate parental knowledge often lead to underreporting and delayed intervention. Mothers, being the primary caregivers, play a crucial role in safeguarding their children through early education, recognition of warning signs, and prompt reporting of suspected abuse. Therefore, the present study aims to assess and enhance the knowledge of mothers regarding child sexual abuse and its prevention, thereby empowering them to create a safe and protective environment for their children.Introduction: Child sexual abuse (CSA) is a global concern with devastating consequences on the physical, psychological, and social wellbeing of children. Prevention of CSA requires awareness and active involvement of parents, particularly mothers, who are the primary caregiver. However, lack of knowledge and awareness often prevents timely recognition and prevention of abuse. Structured educational interventions, such as information booklets, are cost-effective and feasible methods to empower mothers with essential knowledge for safeguarding their children.Aim/ Objectives: The present study was conducted to assess the effectiveness of an information booklet on knowledge regarding prevention of child sexual abuse among mothers.Methodology: A pre-experimental, one-group pre-test post-test design was adopted for the study. A purposive sample of 60 mothers from selected urban areas of Nerchowk, Distt. Mandi (H.P.) was selected. Data were collected using a structured knowledge questionnaire that assessed various aspects of CSA prevention, including meaning, warning signs, risk factors, preventive strategies, and parental role. After the pre-test, an information booklet on prevention of CSA was provided, and post-test knowledge was assessed. Data were analyzed using descriptive and inferential statistics to evaluate the effectiveness of the intervention.Results: The findings indicated that the mean post-test knowledge score of mothers was 79.58% significantly higher compared to their mean pre-test score 52.38%, suggesting an overall improvement in knowledge after exposure to the information booklet. The difference between pre-test and post-test scores was statistically significant (p < 0.05). The results confirmed that the information booklet served as an effective tool in enhancing maternal knowledge regarding prevention of CSA.Conclusion: The study concluded that mother’s knowledge regarding prevention of child sexual abuse can be significantly improved through information booklet. Information booklets, being easy to disseminate and culturally adaptable, can be effectively utilized in community health programs to empower mothers, thereby contributing to the safety and wellbeing of children.
Keywords: Child Sexual Abuse; Knowledge; Prevention; Mothers; Information Booklet